2018
DOI: 10.1590/1678-5150-pvb-5663
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Listeria spp. in cattle and environment of pasture-based dairy farms

Abstract: The aim of the study was to detect Listeria spp., particularly Listeria monocytogenes, in cattle and environment of pasture based dairy farms in Paysandú, Uruguay. A two-stage sampling was conducted, 10 farms were selected by probability proportional to size. A single visit was made to each farm. Samples from bovine faeces, feedstuffs, bulk tank milk, drinking water and soil from the entry and exit pens of the milking parlour were collected for bacteriological studies. PCR assays were used to confirm species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…innocua, shedding this microorganism in the faeces (Hofer & Reis, 2005;Matto et al, 2018). However, there are only two reports of L. innocua as the cause of meningoencephalitis in ruminants (Rocha et al, 2013;Walker et al, 1994), to be contrasted to the numerous reports of animal listeriosis due to L. monocytogenes strains (Walland et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…innocua, shedding this microorganism in the faeces (Hofer & Reis, 2005;Matto et al, 2018). However, there are only two reports of L. innocua as the cause of meningoencephalitis in ruminants (Rocha et al, 2013;Walker et al, 1994), to be contrasted to the numerous reports of animal listeriosis due to L. monocytogenes strains (Walland et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…L. innocua is genetically close to L. monocytogenes , but classically considered non‐pathogenic (Buchrieser et al., 2003 ). It has a wide distribution in the environment, including in ruminant farms as well as in the food industries (Matto et al., 2018 ; Moreno et al., 2012 ). Contradicting the classical idea, it has been shown that haemolytic strains of L. innocua are capable of infecting eukaryotic cells in experimental models like mouse and zebrafish (Moura et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…(33.3%) was reported from vegetables where L. monocytogenes was detected in 22.5% of the vegetables in retail level in Malaysia [ 18 ] and 15.3% in raw vegetable salads collected from Chile [ 19 ]. L. monocytogenes were detected in the feedstuffs (33%) in a dairy farm in Paysandu, Uruguay [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by the pathogenic species of Gram-positive, facultative anaerobic intracellular bacteria of the genus Listeria . Till now, 17 species of the genus have been identified [ 5 , 6 ]. Vestibular ataxia, circling, head tilt, and unilateral cranial nerve deficits are common meningoencephalitis form of the disease seen in small animals such as sheep and goat [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Foetuses from pregnant infected animals are 18 very rich in L. monocytogenes [18]. Similarly, faeces play a significant role in the spread of listeriosis to humans and animals [35]. It is associated with severe foodborne infec tions in humans; thus, this organism is considered one of the most important pathogens responsible for foodborne infections.…”
Section: Introductionmentioning
confidence: 99%